Сучасні технології рухової активності студентів: спортивно-оздоровчий туризм і рекреація - Сергієнко, Юрій Петрович; Гулай, Віктор Степанович; Чаплигін, Василь Петрович; Гаврилюк, Валерій Олексійович; Гаєвий, Вадим Юрійович (Національний педагогічний університет імені М. П. Драгоманова, 2020)
У статті представлено теоретичний аналіз та узагальнено підходи щодо використання засобів спортивнооздоровчого туризму в рекреаційній діяльності (в різних групах населення) і тому числі студентської молоді. На основі теоретичного аналізу та узагальнення навчально-методичної та наукової літератури виявлено, що потреба в руховій активності є актуальною для всього суспільства в цілому. Ефективність застосування технології щодо формування рекреаційної культури студентської молоді з огляду позитивного впливу на показники фізичного стану. В статті обґрунтовано, опрацьовано та визначено структуру і зміст технології формування рекреаційної активності студентської молоді у вищому навчальному закладі засобами оздоровчо-рекреаційної рухової активності. Досліджено різні підходи щодо формування спортивно-оздоровчого туризму, виявлено та розкрито характерні ознаки й особливості активного відпочинку в суспільстві.

The article presents a theoretical analysis and summarizes the approaches on the use of tourism in recreational activities of students. Based on theoretical analysis and synthesis of specified scientificmethodical literature revealed that the need of the youth in active recreation, is an integral part of the harmonious, comprehensively developed personality of a student. In the article, given the present stage of development of the industry of scientific knowledge and on the basis of a comprehensive analysis of concepts and categories of recreation refined interpretation of the concept of "recreational culture" as a component of physical culture. In addition, recreational needs of students systematized. Proved the effectiveness of technology forming recreation culture of students taking into account the positive impact on indicators of physical condition, the theoretical training, the amount of motor activity, the organization of useful leisure and recreation. Substantiation for the structure and content of the technology of forming a recreational activity of students, and defined and developed organizational and methodical conditions of its realization in a higher educational institution means the health and recreational physical activity. The concept of sport tourism, sports and health campaign described. It outlines the main features and challenges of sport tourism, analyzes its types and functions. The article shows various approaches to the definition of this concept identified the characteristics. Classification of sport tourism will thoroughly examine its modifications and main development trends and characteristics, will allow organizing the knowledge and deeply understanding the nature of sport tourism, solving the problems of its territorial organization, to plan the development of the material base, to produce and sell the tourist product. Sports and health tourism plays a significant role in the development of the domestic tourist movement. In fact, it is one of the most accessible mass forms of outdoor activities and ways to discover the world. Today, sport trips are becoming an integral part of the life of all segments of the population. Ukraine has all the prerequisites for the intensive development of sports and recreational tourism: geographical position and topography, favorable climate, rich natural, historical, cultural and tourist-recreational potential.
Keywords: спортивно-оздоровчий туризм; функції спортивно-оздоровчого туризму; фізична рекреація; рекреаційна культура; рекреація; sports tourism; functions of sport tourism; physical recreation; recreation culture; recreation